2016
DOI: 10.1038/ncomms10498
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1 turns into a transcriptional activator by interacting with YAP1 in aggressive cancer types

Abstract: Early dissemination, metastasis and therapy resistance are central hallmarks of aggressive cancer types and the leading cause of cancer-associated deaths. The EMT-inducing transcriptional repressor ZEB1 is a crucial stimulator of these processes, particularly by coupling the activation of cellular motility with stemness and survival properties. ZEB1 expression is associated with aggressive behaviour in many tumour types, but the potent effects cannot be solely explained by its proven function as a transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
236
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(250 citation statements)
references
References 65 publications
(112 reference statements)
12
236
0
2
Order By: Relevance
“…ZEB1 acts as both a transcriptional activator and repressor (Lehmann et al ., 2016; Sanchez‐Tillo et al ., 2011). To clarify the global view of ZEB1‐regulated transcription, we performed RNA‐seq using MDA‐231‐D cells.…”
Section: Resultsmentioning
confidence: 99%
“…ZEB1 acts as both a transcriptional activator and repressor (Lehmann et al ., 2016; Sanchez‐Tillo et al ., 2011). To clarify the global view of ZEB1‐regulated transcription, we performed RNA‐seq using MDA‐231‐D cells.…”
Section: Resultsmentioning
confidence: 99%
“…We examined the ability of EphA2 to enhance transcription of known YAP/TAZ-target genes, Cyr61 , Ctgf , and Inhba (16, 19, 4345) (Fig. 1E).…”
Section: Resultsmentioning
confidence: 99%
“…[5,6] Further, YAP1 participates in many signaling pathways that regulate organic morphology, including ovary enlargement that is one of the major manifestations of PCOS. Genome-wide association studies (GWAS) showed that the single nucleotide polymorphisms of YAP1 (rs11225161, rs11225138, and rs11225166) were significantly different between PCOS and controls and it appears to be a new susceptibility gene for PCOS.…”
Section: Introductionmentioning
confidence: 99%